Phytochemical Composition, Antioxidant, Antimicrobial and in Vivo Anti-inflammatory Activity of Traditionally Used Romanian Ajuga laxmannii (Murray) Benth. (“Nobleman’s Beard” – Barba Împăratului) - Toiu, Anca; Mocan, Andrei; Vlase, Laurian; Pârvu, Alina E.; Vodnar, Dan C.; Gheldiu, Ana-Maria; Moldovan, Cadmiel; Oniga, Ilioara (Frontiers in Pharmacology, 2018)
In the Romanian folk medicine, aerial parts of Ajuga laxmanii (“nobleman’s beard”, Romanian – “barba boierului” or “avrămească” or „creștinească”) is traditionally used as a galactogogue and anti-inflammatory agent. The present study was aimed to evaluate the chemical composition (polyphenols, iridoids, phytosterols), antioxidant, antimicrobial and in vivo anti-inflammatory activity of different extracts of A. laxmanii aerial parts. The major identified bioactive compounds were rutin, 8-O-acetylharpagide and β-sitosterol. The antioxidant activity of A. laxmannii extracts was evaluated using several methods, and the results showed good antiradical effects. Furthermore, the antimicrobial evaluation showed a potent antifungal activity against C. albicans and P. funiculosum. Furthermore, the anti-inflammatory effect was determined by monitoring some parameters involved in the inflammatory process. The results obtained showed differences between the analysed extracts; and therefore the importance of choosing the best solvent in order to extract the appropriate amount of bioactive compounds. A. laxmannii ethanol extract showed an anti-inflammatory effect by reducing total leukocytes, PMN, phagocytosis, and oxidative stress. Compared to diclofenac, only A. laxmannii extract 0.5 had better anti-inflammatory and anti-oxidative stress effects, and this could justify the importance of a correlation between the activity and the used dose. These findings strongly suggest that A. laxmannii could be considered as a valuable source of bioactive compounds, which could be further valued as an anti-inflammatory agent in the composition of several herbal drugs.